PENGARUH PENGUNGKAPAN HAL AUDIT UTAMA, UKURAN PERUSAHAAN, DAN PROFITABILITAS TERHADAP AUDIT REPORT LAG - Yohanes Mario Pratama; Hanny Lusiani (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2024)
Auditors will need to note any major problems found during the audit in 2022 when the Audit Standard on disclosing important audit items is implemented. This process of identifying significant issues affects the audit completion time. In addition to key audit matters, company size and profitability also influence the duration of the audit. This study aims to analyze the impact of disclosing key audit matters, company size, and profitability on audit report lag. The method applied is multiple regression analysis on companies listed on the Indonesia Stock Exchange for the period of 2022-2023. The findings indicate that disclosing key audit matters can shorten audit report lag; the more key audit matters disclosed, the faster the audit process can be completed. Company size has a negative impact on audit report lag, while profitability does not affect audit report lag. The study highlights that shortening audit report lag is crucial for reducing economic uncertainty. When auditors can complete the audit report earlier, stakeholders can make better decisions based on accurate and up-to-date information, thus reducing economic uncertainty and the information gap between management and other stakeholders.